(untitled) (Journal of Geography and Environmental Management, 2018)
Exogenous processes transform the relief of the identified cosmogenic structures within the plains of Turan, the Kazakh melkosopochnik and the mountains of South-East Kazakhstan generally. The main determining indicator features of cosmogenic structures are geomorphological, geological, and structural-tectonic. The degree of change in the initial crater relief depends on the time of formation of cosmogenic structures and the physical and geographical conditions of the territories. Within the meteorite craters, the zonality of the development of the processes of exomorphogenesis is clearly expressed. As a result, the study found that the development of exomorphogenesis in cosmogenic ring structures, as well as in natural mountain systems, corresponds to the law of altitude zonality. The main processes of exomorphogenesis of meteorite craters in the arid zone of Kazakhstan are fluvial processes. The main modern processes include gravity-slope processes, surface flushing, gully and river erosion, processes of complex accumulation.